Tales from Shakespeare : seven plays - Williams, Marcia, 1945- (Cambridge, Mass. : Candlewick Press, 1998)
Retells seven of Shakespeare's plays--Romeo and Juliet, Hamlet, A midsummer night's dream, Macbeth, The winter's tale, Julius Caesar, and The tempest--in comic book format
960
Accelerated Reader AR
Keywords: Shakespeare, William, -- 1564-1616 -- Adaptations; Cartoons and comics